Assessment of knowledge and reasons for medication non-adherence in ambulatory elderly patients with hypertension and diabetes mellitus in a geriatric centre in Nigeria (2021)
Introduction: Hypertension and type 2 Diabetes mel¬litus are global health disorders afflicting millions of elderly patients worldwide with an ever-increasing incidence and prevalence. Non-adherence to medications affects the quality and length of life, and has been associated with negative health outcomes and increasing healthcare costs especially in the elderly [1]. Few empirical data exist on the know¬ledge and medication adherence among elderly patients in sub-Saharan Africa countries. Aim: This study aimed to assess the knowledge, medi¬cation adherence, and the factors associated with patient’s knowledge on diabetes mellitus and hypertension. Methods: A cross-sectional study of 423 elderly patients aged ≥60 years diagnosed with hypertension and diabetes mellitus, selected consecutively at the Geriatric centre in the University College Teaching Hospital, Ibadan was car¬ried out between October 2019 and January 2020. Socio-demographic information, knowledge of the indication of the medications, possible side effects, and details of medi¬cation adherence level with reasons for non-adherence were obtained using interviewer-administered semi-structured questionnaire. Bivariate and multivariate analyses were car¬ried out using SPSS 23. Alpha was set at 0.05. Results: The mean age (±SD) of the older patients was 69.6 ± 6.4 years and 253 (59.8%) were females. About three-quarter of participants (320; 75.7%) were retired. Majority of the elderly (381; 90.1%) were hypertensive, while 270 (63.8 %) were diabetic, and 85 (20.1%) had multimorbidity of both hypertension and diabetes mel¬litus. Patients that were non-adherent with their medication were 138 (32.6%). The most common reasons reported for non-adherence included patient slept off (41; 56.6%), pre-occupation (24; 33.1%) and unavailability of medications (12; 16.6%). Thirty-seven (8.7%) participants intentionally missed doses, out of which 22 (59.5%) reported pill burden as its reason for medication non-adherence. All patients 423 (100.0%) knew the indication for their medications and 20 (4.7%) experienced medication-related side effects. Overall, 299 (70.6%) and 309 (73.0%) of patients with hypertension and diabetes mellitus showed good knowledge about their conditions. Adherence to medication was associated with good knowledge in hypertensive patients (p=0.002), while being male (p=0.002), age-group of 60–69 (p=0.001) and poor adherence (p=0.001) were associated with good knowledge in diabetes mellitus patients. Conclusion: We found non-adherence was mainly as a result of patients’ behaviors, attitude, and unavailability of medications which could be the cause of low medication adherence among the elderly patients. A systematic review on factors associated with medication adherence in older patients reported medication review aimed at simplifying regimens and educating patients about their treatment as intervention.